2005
DOI: 10.1128/iai.73.11.7509-7516.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Strong Antigen-Specific T-Cell Response Is Associated with Age and Genetically Dependent Resistance to Avian Enteric Salmonellosis

Abstract: Chicken genetics and age affect resistance to enteric infection with Salmonella enterica serovar Typhimurium and were used to identify the immune responses that may contribute to rapid clearance. When birds were infected at 40 days of age, line 6 1 chickens cleared the infection more effectively than line N chickens, whereas when birds were infected at 10 days of age, both chicken lines were highly susceptible to infection. Antibody levels, T-cell responsiveness, and cytokine mRNA levels were all elevated duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 49 publications
2
23
1
Order By: Relevance
“…Finally, there was no upregulation of TLR4 or of some of the downstream effectors of TLR4, such as IL-1␤, IL-8, and LITAF (in the resistant line only). This is in clear contrast with what has been reported for the acute phase, during which a massive recruitment of heterophils and macrophages has been observed (43) and the levels of expression of IL-8 and IL-1␤ have been shown to be increased in vitro and in vivo (5,11,17,36). Overall, this suggests that mechanisms responsible for resistance to infection and those involved in resistance to the carrier state are different.…”
Section: Discussioncontrasting
confidence: 55%
“…Finally, there was no upregulation of TLR4 or of some of the downstream effectors of TLR4, such as IL-1␤, IL-8, and LITAF (in the resistant line only). This is in clear contrast with what has been reported for the acute phase, during which a massive recruitment of heterophils and macrophages has been observed (43) and the levels of expression of IL-8 and IL-1␤ have been shown to be increased in vitro and in vivo (5,11,17,36). Overall, this suggests that mechanisms responsible for resistance to infection and those involved in resistance to the carrier state are different.…”
Section: Discussioncontrasting
confidence: 55%
“…It was also shown that after infection with Salmonella the number of CD8 + TCRγδ + T-cells in the chicken intestine increased [6]. CD4 + or CD8 + T-cell responses are not required for the early host response [14], but CD4 + T-cell responses, particularly Th1 responses, play an important role in the clearance of Salmonella from the gastrointestinal tract [5,10,27].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, 43% of hens were seropositive (titre785) after 20 weeks, suggesting flock immunity. The Guildhay method advocates an initial serum dilution of 1:500, whereas similar work with killed Typhimurium vaccines used initial serum dilutions of 1:250, 1:400 and 1:400, respectively (Bailey et al, 2007a;Beal et al, 2005;Withanage et al, 2005). The higher initial dilution may have reduced the number of positive ELISA results in this trial.…”
Section: Discussionmentioning
confidence: 98%